Mengukur Indeks Kepuasan Mahasiswa Fakultas Ekonomi Universitas 45 Surabaya Terhadap Variabel Layanan Akademik - Siti Nurul Hidayah; Aridha Prasetya; Harsono Teguh Santoso; Bambang Karnain; Sugiharto Sugiharto; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research aims to determine the quality of service at the Faculty of Economics, University 45 Surabaya. The population used as subjects in this research was 300 students from the Faculty of Economics, University 45 Surabaya. Determining the sample in this study used probability sampling with proportional sample strata. The results of the analysis using the Importance Performance Analysis (IPA) method show that the services that occur are not running effectively. In the results of the science map graph, there are variables that the faculty should pay special attention to, namely the physical evidence variable. This variable is considered important and is highly expected by students, but the performance shown is low. The variable whose performance must be maintained is the guarantee variable. The variables of responsiveness, reliability and empathy are variables with a low level of hope/importance but the existing performance has been running very well. The author's suggestion is that the faculty continue to maintain the performance of the assurance variable, concentrate more on improving the performance of the physical evidence variable and the responsiveness, reliability and empathy variables which are already running well.